PENENTUAN KUANTITATIF MORFIN DALAM URIN SECARA SPEKTROFOTODENSITOMETRI - Suaniti, N. M.; Hitapretiwi Suryadhi, M. A. (Jurnal Kimia (Journal of Chemistry); Vol. 1, No. 2 Juli 2007)
Quantitative determination of morphine in urine has been done by utilizing spectrophotodensitometry. Morphine standard in methanol 5 g/mL was spotted by linomat between 4-24 L in metal sheet thin layer chromatography spectrophotodensito-metry using morphine standard of 20.40.60.80.100.120. and 140 ng. Methode. statistically and validation analysis, showed a regression line of y = -69.21 + 8.06 x with r = 0.992. Detection and quantitation limits of 18.02 ng and 60.06 ng respectively were measured at maximum wave length of (maks) 287 nm with on recovery of 90.91 percent.
Keywords: morphine, methanol, maximum wave length (maks), thin layer chromatography spectrophotodensitometry